Selective foraging within estuarine plume fronts by an inshore resident seabird - Kowalczyk, Nicole D.; Reina, Richard D.; Preston, Tiana J.; Chiaradia, André (Frontiers in Marine Science, 2015)
The distribution of predators relative to specific abiotic and biotic factors within estuarine plume fronts is largely unexplored due to the lack of fine-scale temporal and spatial oceanographic data. Defining preferred foraging conditions of seabirds in these areas is critical to identifying important foraging habitats. Here, we use data obtained from Ships of Opportunity to improve the way we quantify oceanographic conditions at scales that match marine animal foraging activities within these areas. Using biologgers and data from a Ship of Opportunity, we assessed the fine-scale habitat utilization of the Little Penguin (Eudyptula minor) within an estuarine plume in Victoria, Australia. We assessed how environmental conditions within the home-range (transit and foraging) and core-range (subset area of intensive foraging within the home-range) of this inshore seabird differed to environmental conditions in the accessible, but non-utilized range (i.e. non-foraging range). Penguin foraging ranges occurred in waters with higher Chl-a, turbidity, temperature and lower salinity than non-foraging ranges. High Chl-a biomass was the most important explanatory variable of penguin distribution. Environmental conditions between the core-range and less used home-range also differed. Waters in the core-range were less productive, less turbid and less dynamic. We suggest penguins are foraging in these core-ranges due to the productive yet stable environmental conditions that likely offer a higher degree of prey predictability than the fluctuating conditions in the wider home-range. Furthermore, penguins may spend a greater proportion of their time in core-ranges as these waters have relatively low turbidity and may improve the ability of penguins to detect and capture their prey. Our results highlight the ability of a small-ranging, visual predator to selectively forage in waters with favourable conditions at fine-scales as a potential means to improve foraging efficiency.